Spurious Zipf's Law - Juan-Carlos Candeal; Antonio Monta\~nés; Irene Olloqui (European Regional Science Association (ERSA), 2003)
This paper shows that the acceptance of the Zipf's Law may sometimes be the result of a spurious artifact. By way of some Monte Carlo exercises we provide evidence in favour of the fact that the Zipf's law can be spuriously accepted when the variable being studied is generated by a random distribution. This result is explained by taking account the, so-called, spurious detrending problem.
Keywords: 330